Persepsi masyarakat terhadap kualiti sifat peribadi kepimpinan kepala daerah di Kabupaten Kampar Riau Indonesia - Abu Samah (2016)
Based on the Regional Autonomy Law No. 32 Year 2004, the Districh head in Indonesia are required to possess high personal qualities such as social, religious, and technical qualities. However, in reality, the required natures of personal qualities are rarely practiced and consequently lead to corruptions such as breach of trust, bribery, and fraud. The main objective of this research is to analyze the society's perceptions towards the Kepala Daerah social, religious, and technical nature of their personal qualities in Kabupaten Kampar, Riau. The main interest of this study is to create awareness on the importance of Kepala Daerah personal qualities in performing administrative tasks in their respective district. This field study involved the use of questionnaires and interviews. For the distribution of questionnaires, 5 10 respondents are chosen from three sub-districts namely Kampar Kiri Hulu, Kampar Kiri Hilir and Bangkinang Barat. While for interviews, 205 interviewees are chosen among the community leaders, youth leaders, and religious leaders. The outcome of this research found 56% or majority of the respondents stated that the personal qualities of the Kepala Daerah in Kabupaten Kampar are low. Whereas the lowest personal qualities characteristics are religious personal qualities (56%), follows by social personal qualities (50%), and technical personal qualities (43%). As a result of these weaknesses, the Kepala Daerah are unable to carry out their responsibilities well and hence occurs as one of the factors that affect the development at Kabupaten Kampar, Riau, Indonesia. This research contributes by providing guidelines for the Kepala Daerah in order for them to increase their personal qualities in aspects such as social, religious and technical personal qualities.